THE IMPORTANCE OF TRIAL LESSON TECHNOLOGY IN THE LITERARY EDUCATION PROCESS (ILMIY TADQIQOTLAR VA YANGI OLAM, 2026)
Abstract: This article examines the role and significance of trial lesson technology in the literary education process. Trial lessons serve to develop students’ skills in perceiving literary works, analyzing texts, and thinking independently. This technology enables the application of innovative approaches in education, the integration of theoretical knowledge with practical activities, and the strengthening of interactive cooperation between teachers and students. Through trial lessons, the effectiveness of identifying and assessing students’ knowledge levels, creative potential, and speech culture is enhanced.